Synthesis and Characterization of PEGylated Toll Like Receptor 7 Ligands - Chan, Michael (2011)
Toll like receptor 7 (TLR7) is located in the endosomal compartment of immune cells. Signaling through TLR7, mediated by the adaptor protein MyD88, stimulates the innate immune system and shapes adaptive immune responses. Previously, we characterized TLR7 ligands conjugated to protein, lipid or polyethylene glycol (PEG). Among the TLR7 ligand conjugates, the addition of PEG chains reduced the agonistic potency. PEGs are safe in humans and widely used for improvement of pharmacokinetics in existing biologics and some low molecular weight compounds. PEGylation could be a feasible method to alter the pharmacokinetics and pharmacodynamics of TLR7 ligands. In this study, we systematically studied the influence of PEG chain length on the in vitro and in vivo properties of potent TLR7 ligands. PEGylation increased solubility of the TLR7 ligands and modulated protein binding. Adding a 6–10 length PEG to the TLR7 ligand reduced its potency toward induction of interleukin (IL)-6 by murine macrophages in vitro and IL-6 and tumor necrosis factor (TNF) in vivo. However, PEGylation with 18 or longer chain restored, and even enhanced, the agonistic activity of the drug. In human peripheral blood mononuclear cells, similar effects of PEGylation were observed for secretion of proinflammatory cytokines, IL-6, IL-12, TNF-α, IL-1β and type 1 interferon, as well for B cell proliferation. In summary, these studies demonstrate that conjugation of PEG chains to a synthetic TLR ligand can impact its potency for cytokine induction depending on the size of the PEG moiety. Thus, PEGylation may be a feasible approach to regulate the pharmacological properties of TLR7 ligands.